PENERAPAN KEAMANAN DATA SISWA MENGGUNAKAN INTERNATIONAL DATA ENCRYPTION ALGORITHM (IDEA) DAN RIVEST SHAMIR ADLEMAN (RSA) - Raina Nabila Nizatsary (2022)
A data for an agency or a school must be managed properly and its security must be guaranteed. This research was conducted to increase the security of student data. This research was conducted using symmetric and asymmetric cryptographic methods, namely the International Data Encryption Algorithm (IDEA) and Rivest Shamir Adleman (RSA). The data security process using this method is carried out by first securing student data using a symmetric cryptographic algorithm, namely the International Data Encryption Algorithm (IDEA), then the next data security process secures the key from a symmetric cryptographic algorithm, namely the International Data Encryption Algorithm (IDEA) using the Rivest asymmetric cryptography algorithm. Shamir Adleman (RSA). In this study resulted in a hybrid cryptosystem on a student data which can secure a data well.